Field testing of smart traffic light adaptive traffic control of an intersection using cameras as detectors - Ramos, Ivan Patrick G.; Rosuello, Czar Manuel M.
To address the problems of traffic congestion in the local setting, the Smart Traffic Light System is developed by the UP-EEEI student research. Smart Traffic Light System is an adaptive traffic system that adjusts continuously in real-time based on the vehicle at the intersection by the CCTV cameras. This system optimizes the green time allocation in an intersection. The field test of the Smart Traffic Light System is done at the intersection of University Avenue and c.P. Garcia Avenue. The cameras are installed at the intersection for field testing during which simultaneous traffic surveys are conducted to obtain the data required to solve for the parameters for evaluation which are queue length, vehicle delay, and degree of congestion. The system is assessed and is found to have no significant effect on the degree of congestion of the intersection. The implementation decreased the queue length for the east leg by 14%, the south leg by 31.3% and the west leg by 2.4% compared to when the fixed traffic signal is in effect. The level of service of the intersection is improved by the system, causing the level of service for most volumes to change from LOS B to LOS A. The total delay in the intersection is decreased by an average of 30.9%.